Acoustic-propelled micro/nanomotors and nanoparticles for biomedical research, diagnosis, and therapeutic applications - Mu, Guanyu; Qiao, Yu; Sui, Mingyang; Grattan, Kenneth T. V.; Dong, Huijuan; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Acoustic manipulation techniques have gained significant attention across various fields, particularly in medical diagnosis and biochemical research, due to their biocompatibility and non-contact operation. In this article, we review the broad range of biomedical applications of micro/nano-motors that use acoustic manipulation methods, with a specific focus on cell manipulation, targeted drug release for cancer treatment and genetic disease diagnosis. These applications are facilitated by acoustic-propelled micro/nano-motors and nanoparticles which are manipulated by acoustic tweezers. Acoustic systems enable high precision positioning and can be effectively combined with magnetic manipulation techniques. Furthermore, acoustic propulsion facilitates faster transportation speeds, making it suitable for tasks in blood flow, allowing for precise positioning and in-body manipulation of cells, microprobes, and drugs. By summarizing and understanding these acoustic manipulation methods, this review aims to provide a summary and discussion of the acoustic manipulation methods for biomedical research, diagnostic, and therapeutic applications.